(untitled) (Research, Society and Development, 2024)
The aim of this study is to understand sustainable development from the perspective of contemporary American philosopher Donna Haraway. The search for development permeates various segments, including social, environmental, educational, biological and technological. Through the concept of the cyborg, the theorist reflects the human being of contemporary times, a being who is no longer natural, but endowed with mechanisms and extensions, a subjective being. It is a socially constructed being and, as such, can be reconstructed in relations between humans and non-humans. The research points out that it is in collective action, in what Haraway calls response-ability, in collective accountability, that we will be able to achieve sustainable development. Cyborgs can play an important role in overcoming complex social issues such as machismo, capitalism, rural succession and the production process, given the way we treat the land, the biological nature of human and non-human beings, the way we produce and, consequently, the way we consume. The author presents an innovative vision in that she reflects on and theorises in a broad, complete and complex way about this new moment for humanity, the Anthropocene, with fragmented relationships that could lead us to an unsustainable world. It is in this new era with so many challenges that humans can rebuild themselves.